VD_FINDINFO Décision / 2015 / 850 vom 16. November 2015 - VD Tribunal cantonal (2015)
DÉFENSE D'OFFICE, MOTIVATION DE LA DÉCISION, REJET DE LA DEMANDE | 132 al. 1 let. b CPP (CH), 393 al. 1 let. a CPP (CH)